Women driving a car and its role in achieving self-independence and raising the level of quality of life among a sample of working women in the city of Jeddah - Al-Gamdi, Najwa Abdullah; Alharthi, Suha Omar (Journal of Humanities & Social Sciences, 2024)
The study aimed to identify women's driving and its role in achieving self-independence and raising the quality of life among a sample of women Female workers in the city of Jeddah, and it was applied to a sample of (100) working women. The researcher used the descriptive analytical method, and the Using the Autonomy Scale prepared by Raban and Connell (1989), and the Quality of Life Scale prepared by the World Health Organization (1992) The results of the study showed that women driving cars play a role in achieving autonomy to a moderate degree, as it obtained an arithmetic average Its amount is (38,06) out of the total score of the scale (51), and represents (74,63%), that is, an average level, and that women driving a car has a role in Raising the level of quality of life to a high level, as it obtained an arithmetic average of (3,42), representing quality of life at a rate of (68,40) That is, at a high level, and there are no statistically significant differences between the averages of the responses of the study sample members on the dimensions of the autonomy scale This is attributed to the variable (age - marital status), and there are statistically significant differences between the averages of the responses of the study sample members on the dimensions Quality of life measure attributed to the variable (age) There are no statistically significant differences between the averages of the responses of the study sample members regarding the dimensions The quality of life measure is attributed to the variable (marital status), and in light of the results reached by the study, the researcher recommends designing training programs Guidance and verifying its effectiveness in developing the quality of life among working and non-working women.
Keywords: women's leadership; autonomy; quality of life; working women